Outpatient parenteral antimicrobial therapy: how young is too young?. Issue 10 (10th May 2022) - Hodgson, Kate Alison; Lim, Ruth; Huynh, Julie; Nind, Ben; Katz, Naomi; Marlow, Robin; Hensey, Conor C; Scanlan, Barry; Ibrahim, Laila F; Bryant, Penelope A
Abstract : Objective: To report the use, and assess the efficacy and outcomes of outpatient parenteral antimicrobial therapy (OPAT) in neonates (≤28 days of age), compared with older infants (1–12 months of age). Design: A prospective 8-year observational study from September 2012 to September 2020. Setting: The Hospital-in-the-Home (HITH) programme of the Royal Children's Hospital Melbourne. Patients: Neonatal patients (≤28 days of age) were compared with older infants (1–12 months of age) receiving OPAT. Interventions: Data were collected including demographics, diagnosis, type of venous access and antibiotic choice. Main outcome measures: Success of OPAT, antibiotic appropriateness, complications and readmission rate. Results: There were 76 episodes for which neonates were admitted to HITH for OPAT, and 405 episodes for older infants. Meningitis was the most common diagnosis in both groups (59% and 35%, respectively); the most frequently prescribed antibiotic was ceftriaxone for both groups (61% and 49%). A positive bacterial culture was less frequent in neonates (38% vs 53%, p=0.02). Vascular access complication rate was 19% in neonates compared with 13% in older infants (p=0.2) with no central line-associated bloodstream infection in either group. Rates of appropriate antibiotic prescribing were similarly high between groups (93% vs 90%, p=0.3). The OPAT course was successfully completed in 74 of 74 (100%) neonates and 380 of 396 (96%) older infants (p=0.09). The unplanned readmission rate was low: 4 of 76 (5%) neonates and 27 of 405 (7%) older infants. Conclusions: OPAT is a safe and effective way of providing antibiotics to selected clinically stable neonatal patients. While appropriate antibiotic use was common, improvements can still be made. Abstract : A prospective 8-year observational study from September 2012 to September 2020 including 76 episodes for which neonates were admitted to the Hospital-in-the-Home (HITH) for outpatient parenteral antimicrobial therapy (OPAT), and 405 episodes for older infants evaluated the use, the efficacy and the outcomes of OPAT in neonates (≤28 days of age), compared with older infants (1-12 months of age). This study demonstrates that OPAT is a safe and effective way of providing antibiotics to selected clinically stable neonatal patients. Whilst appropriate antibiotic use was common, improvements can still be made.